The Moderns 1945-1975 : Bacon - Newman - Hamilton - Matisse - Rothko - Kline - Pollock - Sutherland - de Stael - Riley - Warhol (London : Phaidon Press Limited, 1976)
Adami, Valerio ; Anuszkiewicz, Richard ; Arnatt, Keith ; Auerbach, Frank ; Bacon, Francis ; Baziotes, William ; Blake, Peter ; Boshier, Derek ; Bratby, John ; Burri, Alberto ; Caulfield, Patrick ; Cohen, Bernard ; Cook, Barrie ; Davie, Alan ; Denny, Robyn ; Dibbets, Jan ; Dubuffet, Jean ; Francis, Sam ; Frankenthaler, Helen ; Freud, Lucian ; Frost, Terry ; Fulton, Hamish ; Giacometti, Alberto ; Gilbert & George ; Goings, Ralph ; Gorky, Arshile ; Gottlieb, Adolph ; Guston, Philip ; Hamilton, Richard ; Henderson, Nigel ; Heron, Patrick ; Hilton, Roger ; Hitchens, Ivon ; Hockney, David ; Hofmann, Hans ; Hoyland, John ; Indiana, Robert ; Johns, Jasper ; Kelly, Ellsworth ; Kidner, Michael ; Kitaj, R.B. ; Klein, Yves ; Kline, Franz ; de Kooning, Willem ; Lanyon, Peter ; Lichtenstein, Roy ; Louis, Morris ; Mathieu, Georges ; Matisse, Henri ; Motherwell, Robert ; Newman, Barnett ; Nicholson, Ben ; Nolan, Sidney ; Noland, Kenneth ; Oldenburg, Claes ; Olitski, Jules ; Pasmore, Victor ; Pearlstein, Philip ; Phillips, Peter ; Phillips, Tom ; Pistoletto, Michelangelo ; Pollock, Jackson ; Ramos, Mel ; Rauschenberg, Robert ; Riley, Bridget ; Rosenquist, James ; Rothko, Mark ; Scott, William ; Smart, Jeffrey ; Smith, Jack ; Smith, Richard ; Soulages, Pierre ; de Staël, Nicholas ; Steele, Jeffrey ; Stella, Frank ; Still, Clyfford ; Sutherland, Graham ; Tàpies, Antoni ; Tilson, Joe ; Tobey, Mark ; Vasarely, Victor ; Walker, John ; Warhol, Andy ; Wesselmann, Tom ; Wyeth, Andrew ; Wynter, Bryan
Engels
boek